Cognitive and linguistic components of reading acquisition in Turkish: Evidence from second and fourth graders - Bektaş, Sezen. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2017., 2017)
The present study investigated the role of cognitive and linguistic components of reading acquisition in Turkish, with special reference to phonological awareness (PA), rapid automatized naming (RAN), morphological awareness (MA) and phonological memory (PM) in predicting real word reading (WREAD) and non-word reading (NWREAD) abilities of Turkish-speaking children. In a cross-sectional study design, it explored the relationships between the respective reading components and measures with a special focus on grade-level differences. Besides, the relative importance of the variables in predicting word-level reading success was investigated through multiple hierarchical regression analyses across grades. A total of 87 Turkish-speaking children from Grade 2 and 4 participated in the study. Multiple instruments were used to collect the data. The results showed that the fourth graders performed significantly better than the second graders at all the measures, which pointed to a significant grade-level difference between the groups. When WREAD was the dependent variable, regression analyses revealed that RAN was a strong predictor of the WREAD ability at both grades. In addition, PA made a significant contribution to WREAD at Grade 2, whereas it did not account for significant amounts of variance in WREAD at Grade 4. As for NWREAD, none of the predictors made a significant contribution to NWREAD at Grade 2, while RAN appeared as the only significant predictor at Grade 4. The results highlighted that RAN remained as a strong predictor of both reading abilities as the grade level increased; however, the effect of PA tended to decrease over years.
Keywords: Reading -- Phonetic method.; Reading -- Turkey.